Quantitative Estimation of Leaf Heat Transfer Coefficients by Active Thermography at Varying Boundary Layer Conditions - Albrecht, Hendrik; Fiorani, Fabio; Pieruschka, Roland; Müller-Linow, Mark; Jedmowski, Christoph; Schreiber, Lukas; Schurr, Ulrich; Rascher, Uwe (Frontiers in Plant Science, 2020)
Quantifying heat and mass exchanges processes of plant leaves is crucial for detailed under-standing of dynamic plant-environment interactions. The two main components of these pro-cesses, convective heat transfer and transpiration, are inevitably coupled as both processes are restricted by the leaf boundary layer. To measure leaf heat capacity and leaf heat transfer co-efficient, we thoroughly tested and applied an active thermography method that uses a transi-ent heat pulse to compute τ, the time constant of leaf cooling after release of the pulse. We validated our approach in the laboratory on intact leaves of spring barley (Hordeum vulgare) and common bean (Phaseolus vulgaris), and measured τ-changes at different boundary layer conditions. By modelling the leaf heat transfer coefficient with dimensionless numbers, we could demon-strate that τ improves our ability to close the energy budget of plant leaves and that modelling of transpiration requires considerations of convection. Applying our approach to thermal im-ages we obtained spatio-temporal maps of τ, providing observations of local differences in thermal responsiveness of leaf surfaces. We propose that active thermography is an informative methodology to measure leaf heat transfer and derive spatial maps of thermal responsiveness of leaves contributing to improve models of leaf heat transfer processes.